Investigating the Role of Microcredit on Agricultural Output in Rural-Bangladesh - Md. Imrul Hasan; Tanbir Hossain; Sree. Dip Kumar Moholdar; Md. Sohel Rana (Annals of the University of Craiova for Journalism, Communication and Management)
Microcredit or Microfinance is being considered as one of the investment-sources for local farmers who want to cultivate their land. It is highly difficult for local-farmers to collect fund for field-level investment, these farmers select micro-credit loan for seasonal-basis. The research-study attempts to explore the impact of microcredit on agricultural output. Based on a stratified random sampling technique, a total of 200 farmers in the south-west region of Bangladesh are surveyed to address the study objective. Half of the surveyed farmers are microcredit borrowers, while the rest are non-borrowers. The study findings indicate that the average agricultural output of microcredit takers is significantly higher than that of the microcredit non-takers. In the multiple regression model, educational status (ES), land Size (LS), Total Family Income (TFI), Micro-credit takers has positive and significant connection with agro-output. Inversely, yearly Family expenses affects negatively on agro-output. Within this research, ES and LS are statistically significant at 1 percent level. The author considers dummy variables as microcredit takers or non-takers, micro-credit taking farmers produce more agricultural-output compared than non-takers. A long-term sustainable agricultural-policies and green-cultivation are the major challenges for farmers.